The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.12911/22998993/65459
|View full text |Cite
|
Sign up to set email alerts
|

An Impact of the Efficient Functioning of the Ventilation and Air-Conditioning System on Thermal Comfort of the Medical Staff in the Operating Room

Abstract: Ventilation and air conditioning systems are necessary for developing proper parameters of indoor environment in operating rooms. The main task of ventilation and air conditioning in those specific areas consists in creating desirable temperature, reducing the number of microorganisms and the concentrations of hazardous gases and substances in the air, as well as ensuring the proper direction of airflow. In Poland, indoor environment in operating rooms has to comply with the requirements set out in three regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In our study, the number of perioperative personnel who reported satisfaction with the thermal environment was significantly lower among those wearing additional clothing than among those who were not wearing it. Other studies have confirmed that the properties of surgical clothes and wearing additional protective clothing (eg, lead aprons) affect thermal comfort …”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…In our study, the number of perioperative personnel who reported satisfaction with the thermal environment was significantly lower among those wearing additional clothing than among those who were not wearing it. Other studies have confirmed that the properties of surgical clothes and wearing additional protective clothing (eg, lead aprons) affect thermal comfort …”
Section: Discussionmentioning
confidence: 88%
“…Patients generally prefer warmer temperatures than health care personnel . The unique structure of an OR affects the thermal comfort levels of perioperative personnel …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations